1996
DOI: 10.1002/(sici)1097-4547(19960201)43:3<299::aid-jnr5>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Co-localization of NG2 proteoglycan and PDGF ?-receptor on O2A progenitor cells in the developing rat brain

Abstract: A detailed comparison in the developing rat central nervous system between the distribution of the NG2 proteoglycan and the α‐receptor for platelet‐derived growth factor (PDGF) shows that these two molecules are co‐expressed by glial progenitor cells of the O2A lineage and can serve as reliable markers for identification of O2A cells in vivo. Our mapping experiments indicate that NG2‐positive, PDGF α‐receptor positive O2A cells are abundant throughout the developing central nervous system in both white and gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
398
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 594 publications
(427 citation statements)
references
References 65 publications
(54 reference statements)
29
398
0
Order By: Relevance
“…3G-J, arrows), indicating that astrocytes retain expression of m-Msi-1, whereas it is not expressed in differentiated or immature neurons and oligodendrocytes. Some antigenic markers have been used for analysis of the sequential differentiation of oligodendrocytes from dividing precursors, including O-2A progenitor cells, into quiescent oligodendrocytes in vitro and in vivo (Hardy and Reynolds, 1991;Nishiyama et al, 1996). PDGF␣-R is expressed in the developing and adult rodent CNS by the O-2A oligodendrocyte progenitors and preoligodendrocytes (Pringle et al, 1992;Ellison and de Vellis, 1994;Nishiyama et al, 1996).…”
Section: T He White Mattermentioning
confidence: 93%
See 1 more Smart Citation
“…3G-J, arrows), indicating that astrocytes retain expression of m-Msi-1, whereas it is not expressed in differentiated or immature neurons and oligodendrocytes. Some antigenic markers have been used for analysis of the sequential differentiation of oligodendrocytes from dividing precursors, including O-2A progenitor cells, into quiescent oligodendrocytes in vitro and in vivo (Hardy and Reynolds, 1991;Nishiyama et al, 1996). PDGF␣-R is expressed in the developing and adult rodent CNS by the O-2A oligodendrocyte progenitors and preoligodendrocytes (Pringle et al, 1992;Ellison and de Vellis, 1994;Nishiyama et al, 1996).…”
Section: T He White Mattermentioning
confidence: 93%
“…Some antigenic markers have been used for analysis of the sequential differentiation of oligodendrocytes from dividing precursors, including O-2A progenitor cells, into quiescent oligodendrocytes in vitro and in vivo (Hardy and Reynolds, 1991;Nishiyama et al, 1996). PDGF␣-R is expressed in the developing and adult rodent CNS by the O-2A oligodendrocyte progenitors and preoligodendrocytes (Pringle et al, 1992;Ellison and de Vellis, 1994;Nishiyama et al, 1996). Similarly, NG2, a core membrane protein associated with chondroitin sulfate proteoglycan, is also expressed in mitotic O-2A progenitor cells localized in the gray and white matter of perinatal to adult rat brain and disappears as these cells differentiate into oligodendrocytes (Stallcup and Beasley, 1987;Nishiyama et al, 1996).…”
Section: T He White Mattermentioning
confidence: 96%
“…Of these, Abcb1a is a membrane transporter whereas the others are involved in development [41]. Chrna3, Cspg4, Daam2, and Gfra3 play roles in nervous system development [42][43][44][45][46], while Aebp1 is required for smooth muscle formation [47][48][49][50]. We verified the low level of DNA methylation in two different ESC lines, which contrasted with the high DNA methylation level (90%-98% methylated CpGs) in two EpiSC lines (Fig.…”
Section: Identification and Characteristics Of Differentially Methylamentioning
confidence: 99%
“…Studies on experimental glioma using the RCAS/tv-a model have shown that neural/glial stem cells in Ntv-a mice and neural stem cells/astrocytes in Gtv-a mice have the capacity to generate gliomas Holland and Vermus, 1998). The majority of induced tumors in both Ntv-a and Gtv-a mice were positive for NG2 chondroitin sulfate proteoglycan (NG2), a marker of early oligodendrocyte progenitor cells (OPCs) (Stallcup and Beasley, 1987;Pringle and Richardson, 1993;Nishiyama et al, 1996;Polito and Reynolds, 2005). This implied that the OPCs could represent the optimal level of cellular differentiation for oncogenic transformation to occur.…”
Section: Introductionmentioning
confidence: 99%